A new optical low coherence reflectometry device for ocular biometry in cataract patients. Issue 7 (19th April 2009) - Buckhurst, P J; Wolffsohn, J S; Shah, S; Naroo, S A; Davies, L N; Berrow, E J
Abstract : Background: A new commercially available optical low coherence reflectometry device (Lenstar, Haag-Streit or Allegro Biograph, Wavelight) provides high-resolution non-contact measurements of ocular biometry. The study evaluates the validity and repeatability of these measurements compared with current clinical instrumentation. Method: Measurements were taken with the LenStar and IOLMaster on 112 patients aged 41–96 years listed for cataract surgery. A subgroup of 21 patients also had A-scan applanation ultrasonography (OcuScan) performed. Intersession repeatability of the LenStar measurements was assessed on 32 patients Results: LenStar measurements of white-to-white were similar to the IOLMaster (average difference 0.06 (SD 0.03) D; p = 0.305); corneal curvature measurements were similar to the IOLMaster (average difference −0.04 (0.20) D; p = 0.240); anterior chamber depth measurements were significantly longer than the IOLMaster (by 0.10 (0.40) mm) and ultrasound (by 0.32 (0.62) mm; p<0.001); crystalline lens thickness measurements were similar to ultrasound (difference 0.16 (0.83) mm, p = 0.382); axial length measurements were significantly longer than the IOLMaster (by 0.01 (0.02) mm) but shorter than ultrasound (by 0.14 (0.15) mm; p<0.001). The LensStar was unable to take measurements due to dense media opacities in a similar number of patients to the IOLMaster (9–10%). The LenStar biometric measurements were found to be highly repeatable (variability ⩽2% of average value). Conclusions: Although there were some statistical differences between ocular biometry measurements between the LenStar and current clinical instruments, they were not clinically significant. LenStar measurements were highly repeatable and the instrument easy to use.